Can Physical Education be decolonial? - Larissa Michelle Lara (Journal of Physical Education (Maringá), 2025)
This essay proposes to raise reflections on 'other' ways of thinking about and intervening in physical education, starting with the following question: can physical education be decolonial? Through authors who problematize modernity and envision a decolonial project that recognizes and values diverse bodies, the text proposes a reflective debate on the possibility of a just physical education committed to overcoming subalternity. In this process, questions are raised about modernity and its segregationist aspects, the decolonial traits present in Brazilian physical education (notably in the 1990s), and perspectives for a decolonial physical education through embodied practices.